2015
DOI: 10.1074/jbc.m114.605063
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Receptor Overexpression in Mesenchymal Stem Cells Facilitates Treatment of Acute Lung Injury in Rats

Abstract: Background:The utility of mesenchymal stem cells (MSCs) in the treatment of acute lung injury (ALI) is dependent on their ability to reach the sites of tissue damage. Results: Transduction of CXCR4 conferred efficient mobilization of MSCs. Conclusion: CXCR4 overexpression in MSCs facilitated treatment of ALI. Significance: Overexpression of CXCR4 may improve the therapeutic potential of MSCs for the treatment of diseases with tissue damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 52 publications
(52 reference statements)
4
102
0
Order By: Relevance
“…The cellular responses are complex, and, in most cases, the pretreatment procedure affects a great number of factors, and not only a single, specific molecule or protein. In contrast, it should be mentioned that another approach to enhance the release of a specific regenerative factor is to overexpress a single factor in MSCs [70,71,72,73,74]. Nevertheless, these genetically engineered MSCs are not reviewed in this article.…”
Section: Concepts Of Msc Preconditioningmentioning
confidence: 99%
“…The cellular responses are complex, and, in most cases, the pretreatment procedure affects a great number of factors, and not only a single, specific molecule or protein. In contrast, it should be mentioned that another approach to enhance the release of a specific regenerative factor is to overexpress a single factor in MSCs [70,71,72,73,74]. Nevertheless, these genetically engineered MSCs are not reviewed in this article.…”
Section: Concepts Of Msc Preconditioningmentioning
confidence: 99%
“…Moreover, one study has demonstrated that facilitating the homing of MSCs to injured lung tissue led to incremental therapeutic benefits. 31 As a response to tissue inflammation, prostaglandin E 2 (PGE 2 ) biosynthesis is upregulated to a large extent. Also, PGE 2 has been shown to promote the migration of MSCs in vitro by stimulation of the EP2 receptor.…”
Section: Mscs-ep2 Treatment For Lung Injurymentioning
confidence: 99%
“…Yang and colleagues demonstrated that the chemokine SDF-1, and the corresponding chemokine receptor 4 (CXCR4), were involved in MSC migration into injured lung tissue and that the overexpressed CXCR4 in MSCs largely improved lung repair in ALI rat models. 41 The increased homing of MSCs to injured lung tissue is the fundamental mechanism of this incremental beneficial effect. However, the precise mechanism is yet an enigma that necessitates further studies.…”
Section: Mscs-ep2 Treatment For Lung Injurymentioning
confidence: 99%
“…This migration and homing potential without tumorigenic potential has been described in different disease [41,42] and in BPD models previously [38,43]. Chemokines with chemokine receptors CXCR3, CXCR4 and CXCR6 were identified as the key players responsible for cell homing [44]. Further, CXCR4 ligands such as stromal cell-derived factor-1a (SDF-1a) promote MSCs' migration to the injury site [45].…”
Section: Mscs and Bpdmentioning
confidence: 94%